Trends in antimicrobial susceptibility patterns of bacterial isolates in Lahore, Pakistan - Khalid, Nauman; Akbar, Zunaira; Mustafa, Nosheen; Akbar, Jamshaid; Saeed, Shanawar; Saleem, Zikria (Frontiers in Antibiotics, 2023)
Abstract Background Antimicrobial resistance (AMR) has provoked as a global health issue. Antimicrobial stewardship programs should be executed to overcome this issue. The aim of this study was to determine the sensitivity pattern of WHO Aware group antibiotics that assists in selection of appropriate empiric antibiotic therapy. Method A descriptive, cross sectional study was conducted for 6 month duration in which 422 culture sensitivity sample reports from hospital's laboratory were obtained through convenient sampling technique and sensitivity pattern of 9 offending bacteria to the WHO Aware group antibiotics were determined. Descriptive statistics and differences in frequency distribution among the categorical variables were performed using SPSS version 21. Results Among 422 culture sensitivity sample reports, E.coli (16.1%) was the most common gram-negative pathogen. Acinetobacter, E.coli, Klebsiella, Pseudomonas showed 100% sensitivity to polymyxin-b and colistin. Proteus showed highest sensitivity to meropenem (90%), Staph. aureus showed 98% sensitivity to linezolid, Staph.epidermidis was 100% sensitive to vancomycin and linezolid whereas Streptococcus showed highest sensitivity to penicillin (100%) and vancomycin (94.7%). Polymyxin b and colistin were found to be most effective antibiotics against gram-negative bacteria (100%). Gram-positive bacteria were highly susceptible to linezolid (99.4%), vancomycin (98.2%), chloramphenicol (89.5%) and tigecycline (82.6%).